Mechanobiology of the intervertebral disc. (November 2002) - Lotz, J. C.; Hsieh, A. H.; Walsh, A. L.; Palmer, E. I.; Chin, J. R.
Abstract : Intervertebral disc degeneration has been linked in humans to extreme spinal loading regimens. However, mechanisms by which spinal force influences disc cellularity, morphology and consequently biomechanical function are unclear. To gain insight into mechanobiological interactions within the disc, we developed an in vivo murine tail-compression model. Results from this model demonstrate how deviations in spinal stress induce a cycle of altered cell function and morphology as the disc remodels to a new homoeostatic configuration.